Evaluation of renal vasculature and its variants by CT angiography - Bala Murali Krishna Patibandla; Mriganka Deuri Bharali; Ershad Hussain Galeti; Saqib Shahab (Asian Journal of Medical Sciences, 2022)
Background: Kidneys are a pair of retroperitoneal organs supplied by a single renal artery and vein. However, the classic illustration of the renal vasculature, formed by one renal artery and one renal vein, occurs in ≤25% of cases. MDCT angiography is presently the most preferred investigation for assessing prospective renal donors.